Analisis Stigma Terhadap Penderita Gangguan Mental Dikalangan Mahasiswa D-III Keperawatan - Taufik Taufik; Aulina Adamy; Marthoenis Marthoenis; Said Devi Elvin; Roma Sitio; Munazar Munazar (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2020)
Stigma is a situation in which giving someone else a slave that unwittingly demean someone who has been socially discredited. During this time when students see or meet people with mental disorders, they are still afraid and they call the mental disorders people as a crazy man. Stigma can cause people with mental disorders to feel ashamed, blame themselves, despair, and reluctant to seek or receive help. This type of research is analytic descriptive using a cross sectional study design. The sample of this research is the D-III Nursing Banda Aceh students and the Nursing Students at Academy Iskandar Muda Banda Aceh, Data collection was conducted on 06-12 February 2020. Then the data were analyzed by univariate analysis, bivariate analysis with chi square test, and multivariate analysis with using logistic regression test. The results showed that the stigma of Nursing D-III students was high for people with mental disorders (59.11%) and there was a relationship between triggering factors and student stigma. Trigger factors based on stereotypes (p = 0.001), blame (p = 0.001), prejudice (p = 0.001), authoritarianism (p = 0.001), lack of awareness (p = 0.001) and social judgment (p = 0.007). The factors that showed the most significant relationship were stereotypes (p = 0.001 OR 4.44), prejudice (p = 0.001 OR 37.20) and authoritarianism (p = 0.001 OR 6.20). It can be concluded that Nursing D-III students still have a high stigma towards people with mental disorders and they are expected to increase their understanding of mental disorders. Also the education management needs to improve scientific activities or training that are more focused on mental disorders. if the stigma can not be removed, especially on students or health workers in general, it will be very difficult to reduce the number of people with mental disorders (recovered).